Flexible and Contextual Cloud Applications in Mobile Learning - Hashimova, Albina; Prasolov, Valeriy; Burlakov, Vyacheslav; Semenova, Larisa (International Journal of Interactive Mobile Technologies (iJIM), 2020)
The aim of the article is to study the modern mobile learning system, to understand its advantages and disadvantages, and to determine the relationship between the concepts of digital learning. The goal of the study is to conduct an experiment on the implementation of a flexible mobile application for studying the "macroeconomics" by students of economic specialties and to compare the results obtained with the selected control group. A total of 20 sophomores (10 each from two universities: Sechenov University, Department of Economics and Management; and Azerbaijan State Economic University, Department of Economic Theory) were offered to study the course in macroeconomics using a mobile application during the semester (from September to December 2019). Students were selected from two universities for the scientific objectivity and from the second year of the bachelor's degree, since "macroeconomics" is studied in the early courses, regardless of the further, specific economic direction of the student. Students did not attend lectures and practical classes with a teacher; all training was performed with the help of an application. A control group of the same specialty and year (also 20 people) was selected to confirm or contradict the effectiveness of such a mobile application. The control group students studied "macroeconomics" in the traditional way, namely attending lectures and practical classes with a teacher, during this semester. As a result of the experiment, the study group students liked training with the application. Meanwhile, 70% of the students would not like to have such training for all disciplines, permanently. But students supported studying using a special mobile app as a supplement to the main format of teaching. During the final examination, held by the traditional method (a written exam - answers to 4 open questions and 10 multiple choice questions), the following results were obtained. Students, who were using m-learning, on average, got higher results by 0.2 points, according to the overall assessment, a 5-grade scale, and separately according to the test results more by 2 correct answers than students with the traditional education. Thus, this can be explained since students using mobile app practiced material in a form of game or case, which helped them to immerse themselves more in the problem and to assimilate the material. The results were compared with the research of other scientists.